EFFECT OF VARIOUS CARBON SOURCES ON THE GROWTH PROPERTIES AND MORPHOLOGY OF SPIRULINA PLATENSIS (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Cyanobacteria generate biomass under photoautotrophic conditions during photosynthesis. Cultivation of cyanobacteria under photoheterotrophic conditions using various organic carbon sources can increase yield of biomass. In the current study, the effect of organic carbon sources on the growth properties and morphology of cyanobacteria Spirulina platensis, as well as the production of the photosynthetic pigments: chlorophyll a, carotenoids, and phycocyanin were investigated. Carbon sources, such as glucose, fructose and succinate, caused not only an increase in the cyanobacterial growth rate, but also morphological changes in S. platensis trichomes. An increase in the amounts of photosynthetic pigments was also observed. Thus, glucose, fructose, and succinate are more efficient substrates for photoheterotrophic cultivation of these cyanobacteria.
Keywords: Spirulina platensis; carbon sources; photoheterotrophic growth; morphology; pigments content